2021
DOI: 10.3390/ijerph18020791
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Evidence on Eco-Friendly Advertisement Appeals and Intention to Use Bio-Nanomaterial Plastics: Institutional Collectivism and Performance Orientation as Moderators

Abstract: Plastic waste management has become a serious environmental and health concern owing to large amounts of plastic deposits globally. Recently, innovative and sustainable solutions have been introduced (e.g., bio-nanomaterial plastics) to overcome the growing environmental threats. Hence, green marketers need to develop effective advertising campaigns to enhance the usage of bio-nanomaterial plastics. Past literature has suggested that cultural value-laden advertising appeals can give sustainable behavioral cues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
(109 reference statements)
1
7
0
Order By: Relevance
“…Moreover, the MSV estimates are all less than AVE values. All these factors indicate reliable and valid data as recommended in the literature (Raza et al, 2021;Zaiþ & Bertea, 2011).…”
Section: Convergent and Discriminant Validitysupporting
confidence: 65%
“…Moreover, the MSV estimates are all less than AVE values. All these factors indicate reliable and valid data as recommended in the literature (Raza et al, 2021;Zaiþ & Bertea, 2011).…”
Section: Convergent and Discriminant Validitysupporting
confidence: 65%
“…More importantly, both IC and GC can moderate the relationship between social identity and pro‐environment actions. In other words, the effect of identity can be contingent to the level of collectivism in human collectives (Raza et al, 2021; Tascioglu et al, 2017). For instance, it has been shown that GC can moderate the relationship between social identity and environmental attitudes/behaviors (Uljas, 2001).…”
Section: Theoretical Background and Research Hypothesismentioning
confidence: 99%
“…Additionally, these culturally convergent ad appeals are expected to be trusted as socially accepted concerning the adoption of the advertised product or brand as liked. Scholars noted that SAP advocates that a high congruity or adaption strategy of advertising undertakings is expected to induce one's perceptions of correspondence and heighten the chance of engendering affirmative reactions toward the advertised product [41]. Generally, in designing digital advertising, factors such as norm congruence must be critically analyzed to avoid some kind of conflicting situations that may arise in the mind of the individuals while interpreting its meanings in their cultural perspectives.…”
Section: Literature Review 21 Research Gap and Theoretical Underpinmentioning
confidence: 99%